Seed Heteromorphism: An Important Adaptation of Halophytes for Habitat Heterogeneity - Liu, Ranran; Wang, Lei; Tanveer, Mohsin; Song, Jie (Frontiers in Plant Science, 2018)
Seed germination is a very critical and important step for seedling establishment under saline environments, as high level of salinity in the soil can prevent seed germination. However halophytes exhibit an interesting mechanism to cope with salt stress. Many halophytes produce heteromorphic seeds, which have different dormancy and germination behavior under saline conditions. This characteristic is related to the structural and physiological differences among heteromorphic seeds. It was unclear that how heteromorphic seeds differently accumulate organic and inorganic substances under saline conditions, and what are the physiological and molecular mechanisms involved in the production of heteromorphic seeds, and in the development of transgenerational plasticity in heteromorphic seeds. In the current brief review, dormancy and germination and the possible role of seed coat and storage compounds in this process of heteromorphic seeds development have been discussed. Moreover, the role of maternal effects on heteromorphic seeds production under saline environments and growth and reproduction capability of the descendants from them have been highlighted.